Hydrogen storage high-entropy alloy coating prepared by laser cladding process and preparation method of hydrogen storage high-entropy alloy coating
The preparation of hydrogen storage high-entropy alloy coating through laser cladding process solves the problems of composition uniformity and difficulty in microstructure control in traditional smelting methods, and achieves efficient hydrogen storage performance and industrial advantages.
Patent Information
- Application Number
- CN202411620735.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-04
AI Technical Summary
The preparation of hydrogen storage high-entropy alloys in traditional smelting methods has problems such as difficult to control components and microstructure, high energy consumption and cooling rate limit, which affects its hydrogen storage performance.
A hydrogen storage high-entropy alloy coating was prepared by laser cladding, and ball milling was performed by mixing powders of Mg, Ti, Nb, V, Zr and other metal elements. Then, a uniform high-entropy alloy coating was formed on the surface of the substrate using laser cladding technology, and rapid cooling and heating were performed.
It realizes excellent hydrogen storage performance of high-entropy alloys, avoids material waste, reduces production costs, has industrial advantages, and promotes the formation of BCC structural phases, improves hydrogen storage capacity and hydrogen absorption kinetic performance.
Smart Images

Figure CN119553265A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloys, and in particular to a hydrogen storage high entropy alloy coating prepared by a laser cladding process and a preparation method thereof. Background Art
[0002] Hydrogen is a clean energy source that is renewable and sustainable, and can reduce global fuel consumption and environmental pollution. The current mainstream hydrogen storage modes are divided into three types: gaseous, liquid, and solid. Gaseous hydrogen storage is usually achieved by compressing hydrogen into high-pressure tanks, which is the most common way of hydrogen storage. However, high-pressure storage has high requirements for the safety and stability of the container, and there is a greater risk of loss during transportation. Liquid hydrogen storage cools hydrogen to below its boiling point to convert it into liquid. This method is suitable for large-scale hydrogen storage, but liquid hydrogen storage has high requirements for energy consumption and hydrogen storage equipment. Solid-state hydrogen storage stores hydrogen in solid materials by adsorption or in the form of compounds. It is safer and can be carried out at temperatures and pressures close to the environment. It has low requirements for energy consumption and equipment and is easy to transport.
[0003] At present, the development and application of traditional solid hydrogen storage alloy systems have reached saturation. The alloys obtained by doping ordinary hydrogen storage alloys with a small amount of other elements have been difficult to meet the requirements of hydrogen storage performance. Hydrogen storage high entropy alloys refer to a class of materials designed using the characteristics of high entropy alloys (HEAs), which are specifically used for efficient storage of hydrogen. High entropy alloys are a new type of alloys composed of five or more metal elements mixed in an equimolar ratio or a near equimolar ratio. The content of each element is between 5% and 35%. It has high entropy effect, cocktail effect, lattice distortion effect and hysteresis diffusion effect. These four effects all play a certain role in obtaining hydrogen storage alloys with excellent hydrogen storage performance. The high entropy effect provides certain conditions for the formation of single-phase solid solutions in high entropy alloys, especially BCC solid solutions, which have higher hydrogen storage capacity and better hydrogen absorption kinetics. In high entropy alloys, the atomic radius of each element is different, which will cause serious lattice distortion in the solid solution, resulting in more lattice gaps, defects and strains, providing more vacancies and channels, which are conducive to the diffusion, dissociation and recombination of hydrogen atoms. When high entropy alloys diffuse, the types of atoms around each lattice are different and the chemical bonds are different. Therefore, the lattice potential barrier fluctuates more during atomic diffusion and the diffusion is slower, which provides a basis for good hydrogen storage capacity. Finally, under the influence of the cocktail effect, all principal elements jointly affect the alloy properties. Due to the diversity of element selection and the controllable element ratio, it is possible to prepare high entropy alloys whose comprehensive properties meet the needs of hydrogen storage applications.
[0004] In terms of hydrogen storage applications, high entropy alloys have shown several important advantages: (1) High hydrogen storage capacity: By selecting appropriate alloy components, the hydrogen storage capacity of the alloy can be improved to achieve a higher hydrogen storage density. (2) Good cyclic stability: This means that the alloy can maintain stable performance during multiple hydrogen absorption and desorption processes, which is very important for practical applications. (3) Appropriate hydrogen absorption and desorption temperature and pressure: By adjusting the alloy composition, hydrogen storage alloys can achieve effective hydrogen absorption and release under mild conditions, which is suitable for vehicle-mounted or other portable energy storage systems. (4) Safety and environmental friendliness: Compared with hydrogen storage in liquid or compressed gas form, solid hydrogen storage is safer and less prone to leakage.
[0005] At present, most of the methods for preparing hydrogen storage high entropy alloys are smelting blocks, which has some potential disadvantages: (1) The problem of composition uniformity: During the smelting process, due to the differences in melting points, boiling points and solubility of different metal elements, the internal composition of the alloy may be unevenly distributed, affecting the performance of the final material. This problem is particularly prominent in high entropy alloys containing multiple elements. (2) Difficulty in controlling microstructure: The microstructure (such as grain size, phase distribution, etc.) of high entropy alloys prepared by smelting is difficult to accurately control. These microstructures have an important influence on the mechanical properties and hydrogen storage properties of the material. (3) High energy consumption: The smelting process requires high-temperature heating, which not only consumes a lot of energy but also increases production costs. For large-scale industrial production, this is an issue that cannot be ignored. (4) Cooling rate limitation: The cooling rate after smelting is usually limited, which may affect the final phase composition and microstructure of the alloy, and thus affect its hydrogen storage performance. Rapid cooling can obtain finer grains and amorphous structures, which is beneficial to improving hydrogen storage performance, but it is difficult to achieve rapid cooling in the smelting method.
[0006] In contrast, the use of laser cladding high-entropy alloy coatings can not only achieve excellent performance, but also avoid material waste, reduce costs, and have more industrial advantages; and the rapid cooling and heating characteristics during the laser cladding process help promote the formation of a BCC (body-centered cubic) structural phase, which has a higher hydrogen storage capacity and better hydrogen absorption kinetics.
[0007] Therefore, the development of a laser cladding hydrogen storage high entropy alloy coating has great application prospects. Summary of the invention
[0008] The first aspect of the present invention provides a hydrogen storage high entropy alloy coating prepared by a laser cladding process, wherein the raw materials for preparing the alloy coating include: Mg, Ti, Nb, V, Zr and M, and M is at least one of Cr, Fe, Mn, Co, Ni, Cu, and Al.
[0009] In some embodiments, the molar ratio of Mg, Ti, Nb, V, Zr and M is (1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2).
[0010] Furthermore, the molar ratio of Mg, Ti, Nb, V, Zr and M is 1:1:1:1:1:1.
[0011] In some embodiments, the purity of Mg, Ti, Nb, V, Zr and M is greater than or equal to 99.9%.
[0012] The applicant found that when the above-mentioned types of alloys are used to prepare the coating, it not only meets the design concept of high entropy alloys, but also has excellent hydrogen storage performance. The reason for the analysis may be that by compounding different alloy components, the crystal structure of the alloy can be adjusted at the microscopic level to form a microenvironment that is more conducive to the adsorption and diffusion of hydrogen atoms, and the addition of the above elements can promote the formation of more grain boundaries and defect sites, which are often easier to capture hydrogen atoms, thereby improving the hydrogen storage efficiency. In addition, the reasonable combination of the above alloy components can also improve the thermodynamic stability of the hydrogen storage material, making the energy change in the hydrogen storage process more moderate, effectively promoting the contact between hydrogen molecules and the alloy surface and the migration of hydrogen atoms inside the alloy, reducing kinetic barriers, and facilitating a rapid and stable hydrogen absorption and desorption cycle.
[0013] In some embodiments, the particle size of Mg, Ti, Nb, V, Zr and M is 100-200 mesh.
[0014] A second aspect of the present invention provides a method for preparing a hydrogen storage high entropy alloy coating, comprising the following steps:
[0015] S1. Preparation of alloy powder: Mix the raw materials for preparing the alloy coating and put them into a ball mill, and prepare high entropy alloy powder after ball milling;
[0016] S2. Laser cladding: High entropy alloy powder is laser clad on the substrate surface by using a powder feeding method to form a uniform cladding layer on the substrate surface;
[0017] S3. Surface finishing: The cladding layer is subjected to coarse grinding and fine grinding in sequence, and then ultrasonically cleaned and dried with anhydrous ethanol. The substrate is packaged and stored in a vacuum box.
[0018] In some embodiments, the rotation speed of the ball mill is 100-200 r / min, and the ball milling time is 0.5-2 h.
[0019] In some embodiments, the powder feeding method is side-axis powder feeding, the powder feeding gas flow rate is 10-15 L / min, and the powder feeding speed is 20-25 g / min.
[0020] In some embodiments, the powder feeding method is specifically as follows: placing the powder stored in the vacuum box into the powder barrel of the powder feeder, turning on the powder feeder switch, adjusting the powder feeding parameters, adjusting the powder feeding speed to 20-25 g / min, opening the argon gas bottle, adjusting the throttle valve to a gas flow rate of 10-15 L / min, and then starting laser cladding.
[0021] In some embodiments, the laser power of the laser cladding is 2-5KW, and the cladding speed is 150-300mm / min.
[0022] In some embodiments, the specific operation steps of the laser cladding are: turn on the voltage stabilizer, PLC control cabinet, turn on the laser, chiller, cladding robot, powder feeder, increase the laser voltage, start the laser cladding experiment: use laser power 2-5Kw, cladding speed 150-300mm / min parameters for laser cladding, after cladding one pass, move the cladding robot, use 30% overlap rate to perform the second laser cladding, and so on for the third pass, the fourth pass... until the entire substrate surface is laser clad into a high entropy alloy, turn off the high voltage, turn off the powder feeder, and the laser cladding ends. In some embodiments, the fine grinding is fine grinding using 180-1000 mesh sandpaper.
[0023] In some embodiments, the substrate is a substrate that has been cleaned of rust and dirt and ultrasonically cleaned with anhydrous ethanol.
[0024] The rapid cooling and heating characteristics used in the laser cladding process of the present invention are helpful to promote the formation of a BCC (body-centered cubic) structural phase, which has a higher hydrogen storage capacity and better hydrogen absorption kinetics.
[0025] The hydrogen storage high entropy alloy MgTiNbVZrM is prepared by laser cladding, which can not only solve the problem of high melting point elements being difficult to melt in the production of high entropy alloys, but also produce a fine and uniform alloy structure, and has the advantages of fast forming rate and high processing efficiency, and has industrial advantages; and the rapid cooling and heating characteristics of this preparation method are conducive to the formation of BCC phases, and the BCC solid solution has a higher hydrogen storage capacity, so the hydrogen storage capacity of the present invention can be further improved.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] By utilizing the method of the present invention, a high entropy alloy coating is prepared on the surface of a substrate by laser cladding, which can not only obtain the excellent hydrogen storage performance of the high entropy alloy, but also avoid material waste, reduce costs, and have industrial advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of overlap ratio in the embodiment. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The overlap rate described in the present invention is defined as follows: after one pass of cladding is completed, the cladding robot is moved and a second pass of laser cladding is performed using a 30% overlap rate, and so on, until the entire substrate surface is laser clad into a high entropy alloy.
[0031] The calculation method is: the area of the second track overlapping the first track ÷ the area of the first track * 100%.
[0032] Example 1
[0033] The present embodiment provides a hydrogen storage high entropy alloy coating prepared by a laser cladding process, wherein raw materials for preparing the alloy coating include: Mg, Ti, Nb, V, Zr and Cr, and the molar ratio is 1:1:1:1:1:1:1.
[0034] The purity of the Mg, Ti, Nb, V, Zr and Cr is 99.9% and the particle size is 100-200 meshes.
[0035] The preparation method of the hydrogen storage high entropy alloy coating comprises the following steps:
[0036] S1. Preparation of alloy powder: The raw materials for preparing the alloy coating are mixed and put into a planetary ball mill for ball milling. The speed of the ball mill is 150 r / min, and the ball milling time is 1 h. After ball milling, a high entropy alloy powder is prepared;
[0037] S2. Laser cladding: High entropy alloy powder is laser clad on the substrate surface by powder feeding method. The powder feeding method is side-axis powder feeding. Argon gas is selected as powder feeding gas. The powder feeding gas flow rate is 12L / min and the powder feeding speed is 22g / min. The laser power is 3KW and the cladding speed is 250mm / min. Multiple parallel overlaps are performed on the sample with an overlap rate of 30%, forming a uniform cladding layer on the substrate surface.
[0038] The specific operation of laser cladding in S2 is as follows: turn on the voltage stabilizer, PLC control cabinet, turn on the laser, chiller, cladding robot, powder feeder, increase the laser voltage, and start the laser cladding experiment: use laser power 2-5Kw, cladding speed 150-300mm / min parameters for laser cladding, after cladding one layer, move the cladding robot, and use 30% overlap rate to perform multiple laser cladding until the entire substrate surface is laser clad into high entropy alloy, turn off the high voltage, turn off the powder feeder, and the laser cladding is completed.
[0039] S3. Surface finishing: The cladding layer is subjected to coarse grinding and fine grinding in sequence, wherein the fine grinding is performed using sandpaper with mesh sizes of 180-1000 (the mesh size increases gradually), and then the surface is ultrasonically cleaned and dried using anhydrous ethanol, and the substrate is packaged and stored in a vacuum box.
[0040] The substrate is made of Q235 steel, which has been derusted and cleaned by ultrasonic cleaning with anhydrous ethanol.
[0041] Example 2
[0042] This embodiment provides a hydrogen storage high entropy alloy coating prepared by a laser cladding process. The specific implementation method is the same as that of Example 1, except that the raw materials for preparing the alloy coating include: Mg, Ti, Nb, V, Zr and Mn, and the molar ratio is 1:1:1:1:1:1:1.
[0043] Example 3
[0044] This embodiment provides a hydrogen storage high entropy alloy coating prepared by a laser cladding process. The specific implementation method is the same as that of Example 1, except that the raw materials for preparing the alloy coating include: Mg, Ti, Nb, V, Zr and Fe, and the molar ratio is 1:1:1:1:1:1.2.
[0045] Comparative Example 1
[0046] The specific implementation of this comparative example is the same as that of Example 1, except that the raw materials for preparing the alloy coating include: Mg, Ti, Nb, V, Zr and Ni, and the molar ratio is 0.5:1:1:0.5:1:2.
[0047] Comparative Example 2
[0048] The specific implementation method of this comparative example is the same as that of Example 1, except that the raw materials for preparing the alloy coating include: Mg, Nb, V, Zr and Al, and the molar ratio is 0.3:1:1.5:1:2.2. The laser power is 1.5 kW and the cladding speed is 400 mm / min.
[0049] Comparison example
[0050] Q235 steel was used as a control example.
[0051] Performance Testing
[0052] The alloy coatings or alloys of the above embodiments and comparative examples were tested for hydrogen absorption performance under the conditions of 298K and 6MPa. The specific test method was as follows:
[0053] The test results are shown in Table 1.
[0054] Table 1
[0055] Hydrogen absorption (wt.%) Example 1 3.61 Example 2 3.58 Example 3 3.53 Comparative Example 1 2.11 Comparative Example 2 1.56 Comparison example 0
[0056] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A hydrogen storage high entropy alloy coating prepared by laser cladding process, characterized in that: The raw materials for preparing the alloy coating include: Mg, Ti, Nb, V, Zr and M, and M is at least one of Cr, Fe, Mn, Co, Ni, Cu and Al.
2. The hydrogen storage high entropy alloy coating according to claim 1, characterized in that: The molar ratio of Mg, Ti, Nb, V, Zr and M is (1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2).
3. The hydrogen storage high entropy alloy coating according to claim 2, characterized in that: The particle sizes of Mg, Ti, Nb, V, Zr and M are 100-200 meshes.
4. A method for preparing a hydrogen storage high entropy alloy coating according to any one of claims 1 to 3, characterized in that: The steps include: S1. Preparation of alloy powder: Mix the raw materials for preparing the alloy coating and put them into a ball mill, and prepare high entropy alloy powder after ball milling; S2. Laser cladding: High entropy alloy powder is laser clad on the substrate surface by using a powder feeding method to form a uniform cladding layer on the substrate surface; S3. Surface finishing: The cladding layer is coarsely ground and finely ground in sequence, and then ultrasonically cleaned and dried with anhydrous ethanol. The substrate is packaged and stored in a vacuum box.
5. The preparation method according to claim 4, characterized in that: The rotation speed of the ball mill is 100-200 r / min, and the ball milling time is 0.5-2 h.
6. The preparation method according to claim 5, characterized in that: In the powder feeding method, the powder is fed in by side-axis feeding, the powder feeding gas flow rate is 10-15 L / min, and the powder feeding speed is 20-25 g / min.
7. The preparation method according to claim 6, characterized in that: The laser power of the laser cladding is 2-5KW, and the cladding speed is 150-300mm / min.
8. The preparation method according to claim 7, characterized in that: The fine grinding is performed using 180-1000 mesh sandpaper.
9. The preparation method according to claim 8, characterized in that: The substrate is cleaned of rust and dirt and ultrasonically cleaned with anhydrous ethanol.